“National idea” in the short stories of Mukhtar Auezov and Kim Dong-in: cognitive perception and narrative analysis - A.D., Alina (Journal of Oriental Studies, 2019)
The author raises the theme of “national idea” in the short stories of Mukhtar Auezov and Kim Dongin. It also considers various cognitive abilities and research methods for a multifunctional analysis of this issue. The features of theories of cognitive literary criticism and their change in the analysis of literary works touched. The author takes as the basis the stories “Savage Grey” and “The red hills,” which most of all compose the semantic and contextual burden for revealing the concept of “national idea.” For revealing the topic, narrative analysis is carried out as one of the methods proposed by the author. Studying this method and simultaneously opening up the reasons for the cognitive perception of the “national idea” by the writers, an extensive analysis of the issue under study is made. The multilateral analysis allows us to understand the course of thought of the writers and the primary purpose of literary works. Also, a comparative narrative analysis of the texts exposes the cultural, historical, and social characteristics of the Kazakh and Korean society during the beginning of the 20th century. Key words: national idea, cognitive literary criticism, narrative, short story, perception, method, theory, analysis.